Segmentation of 2D and 3D textures from estimates of the local orientation - Jeulin, Dominique (Image analysis and stereology, 2008)
We use a method to estimate local orientations in the n-dimensional space fromthe covariance matrix of the gradient, which can be implemented either in the image space or in the Fourier space. In a second step, two methods allow us to detect sudden changes of orientation in images. The first one uses an index of confidence of the estimated orientation, and the second one the detection of minima of scalar products in a neighbourhood. This is illustratedon 2D Transmission Electrons Microscope images of cellulose cryofracture (to display the organisation of cellulose whiskers and the pointsof germination), and to 3D images of a TA6V alloy (lamellar microstructure) obtained by microtomography.
Keywords: Fourierjeva analiza; Image Processing, Computer-Assisted; Mikroskopija elektronska; Fourier Analysis; Cellulose; Slika, obdelava z računalnikom; Celuloza; Microscopy, Electron; mikrostruktura; stereologija; analiza slik